Endovascular management of renal artery aneurysms induced by neurofibromatosis type 1: A case report. Issue 47 (November 2017) - Zhang, Bihui; Zou, Yinghua; Yang, Min; Niu, Guochen
Abstract: Rationale: Neurofibromatosis type 1 (NF-1) is an autosomal dominant disorder characterized by cafe au lait macules and neurofibromatosis. Renal artery aneurysms are relatively uncommon. Endovascular techniques are effective in treating renal aneurysms but successful cases are rarely reported in NF-1 adults. Patient concerns: The patient was one 23-year-old female presented with hypertension, multiple café-au-lait spots ≥15 mm, and plexiform neurofibroma. Renal artery aneurysms were found by ultrasound. Diagnoses: NF-1 was diagnosed based on clinical manifestations and confirmed by gene test. Renal artery aneurysms were diagnosed based on computed tomography. Interventions: Bilateral renal artery angiography was performed and 3 aneurysms were found sequentially on the left anterior superior segmental artery. Microcoil embolization of aneurysms was undertaken. Outcomes: The patient's blood pressure decreased after the procedure with reduction of medicine. A 3-month follow-up unilateral selective renal angiogram demonstrated little change in size of aneurysms, and no opacification of the aneurysmal sac was found. Serum creatinine remained in normal range at 3-month. Lessons: Successful endovascular treatment for NF-1 related renal artery aneurysms in adults is reported for the 1st time with preserved renal function and improved hypertension. Endovascular procedure is considered to be feasible and effective for renal artery aneurysms induced by NF-1.